AN analysis of spatial dispersal in Ceratitis capitata in an orchard of the ‘Palmer’ mango using McPhail traps - Thalia Prado de Castro, Ingrid; Lacerda Lemos, Odair; Aguiar Leite, Suzany; Rafael de Souza, José; Alves Ladeia, Crislaine; Santos Freire, Daniel; Renan de Oliveira Santos, Hosnerson; Leite Silva, Gabriela (Revista Ciência Agronômica, 2023)
Th e aim of this study was to analyse patterns of spatial dispersal in Ceratitis capitata using two types of attractive traps and propose a predictive model of pest dispersal with the aim of determining management zones for decisionmaking. The experiment was conducted in an orchard of the ‘Palmer’ mango in the district of Belo Campo, Bahia. Sampling was carried out using McPhail and Jackson traps. The pattern of spatial dispersal in C. capitata was determined using the Perry and Mead Index of Dispersion, the Morisita Index, and the Local Moran index (LISA). The spatial variability of the abundance of C. capitata was obtained by geostatistical analysis, with the indicator kriging method used to prepare the location and spatial distribution maps. The Perry and Mead Index of Dispersion and the Morisita Index showed an aggregated pattern of spatial dispersal, whereas the Moran Local index showed a random pattern from 7 DFSH (days from the start of the harvest) to 35 DFSH, and an aggregated pattern at 42 DFSH. The SDI was strong at 7 and 35 DFSH and moderate at 14, 28 and 42 DFSH. The dispersal patterns of C. capitata allow an exponential predictive model to be produced, outlining strategies for exponential management zones of C. capitata, and detecting which places have the highest risk of the pest occurring.